Assessment of Indoor Environmental Quality in Sports Halls and Auditoriums in Aceh Province - Nyak Amir; Ibrahim Ibrahim; Herri Darsan (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Indoor environmental quality plays an important role in ensuring safety and comfort in large public facilities such as sports halls and auditoriums. This study aims to analyze oxygen concentration and noise intensity in selected public buildings across Aceh Province, Indonesia. A descriptive mixed-method approach was employed by combining quantitative measurements and qualitative field observations. Oxygen concentration was measured using an oxygen gas sensor connected to Logger pro software, while noise intensity was recorded using a sound level meter. Measurements were conducted at four points in each of twelve buildings. The results show that oxygen concentration in most facilities ranged from 20.3 to 20.7%, indicating conditions that comply with WHO and OSHA safety standards. An anomalous oxygen level exceeding 23.5% was detected in one auditorium, which is likely attributable to instrument calibration error. In contrast, noise intensity frequently exceeded recommended limits, with peak values ranging from 85 dB to nearly 100 dB in several buildings. These findings indicate that while indoor oxygen conditions are generally adequate, noise pollution remains a significant environmental concern in public sports halls and auditoriums